Blanking induced damage in thin 3.2% silicon steel sheets - Diween Hawezy (Production Engineering, 2020)
The cores of electrical motors and transformers are made by blanking, piercing and stacking of thin metallic sheets having various features cut from the original blank. The material experiences local plastic deformation near the cut edge due to the blanking operation. The quality and efficiency of the produced products are directly affected by the mechanical and magnetic properties of the blanks at the cut edge. The effects of the blanking process on deformation evolution in thin sheets of high Si electrical steels was investigated. In-situ blanking experiments together with the digital image correlation (DIC) technique were used to quantify local deformation evolution during thin sheet blanking operations. Magnetic hysteresis losses were measured using a purpose-built single sheet tester and linked to the measured deformation maps. The residual stresses were qualitatively assessed by means of nano-hardness measurements while the local microstructural properties and dislocation generations were determined using EBSD analysis of the blanked parts. The results indicated that for the tested materials with 0.1t blanking clearance, electrical steel sheets with 0.2 mm thickness experiences larger deformation prior to fracture during blanking compared with samples having 0.35 mm thickness. This has a direct relationship with the measured hysteresis losses. However, the dislocation maps indicated that dislocations of GNDs are more pronounced for thicker samples that aligns with the effect of dislocations on magnetic power losses rather than hysteresis losses measured in this research.